Gênero textual narrativo e produções escritas de escolares: contribuições para a apropriação da linguagem - Oliveira, Jáima Pinheiro de [UNESP] (2014)
This paper discusses the conception of textual genres present in the National Curriculum Parameters, regarding our school model, suggesting a program of support for pedagogical practice, the use of narrative genre, from their elements that organize this genre. The written productions of students showed significant growth indicators and ownership of the genre worked.